Diagnostic and prognostic value of scavenger receptor class B type 1 in clear cell renal cell carcinoma. Issue 5 (April 2017) - Xu, Guanghua; Lou, Ning; Xu, Yuchen; Shi, Hangchuan; Ruan, Hailong; Xiao, Wen; Liu, Lei; Xiao, Haibing; Qiu, Bin; Bao, Lin; Yuan, Changfei; Chen, Ke; et al.
Aberrant expression of scavenger receptor class B type 1 has been reported in several human cancers. Nevertheless, the roles of scavenger receptor class B type 1 in clear cell renal cell carcinoma remain unclear. The aim of this study was to evaluate the diagnostic and prognostic value of scavenger receptor class B type 1 in clear cell renal cell carcinoma. The messenger RNA level of scavenger receptor class B type 1 in clear cell renal cell carcinoma tissues was detected by quantitative reverse transcription polymerase chain reaction, while protein level was determined by western blot and immunohistochemistry. The lipid content between clear cell renal cell carcinoma tissues and normal kidney tissues was differentiated by Oil Red O and hematoxylin–eosin staining. The diagnostic value of scavenger receptor class B type 1 was determined by receiver operating characteristic curve. The prognostic significance of scavenger receptor class B type 1 was assessed by Kaplan–Meier analysis and Cox regression analysis. Our results showed that the expression of scavenger receptor class B type 1 in clear cell renal cell carcinoma tissues at both messenger RNA and protein level was much higher than that in normal kidney tissues. Receiver operating characteristic curve analysis exhibited a significant value of area under the curve (0.8486, 95% confidence interval: 0.7926–0.9045) with strong sensitivity (0.75, 95% confidence interval: 0.6535–0.8312) and specificity (0.90, 95% confidence interval: 0.8238–0.9510). Kaplan–Meier analysis revealed that patients with higher scavenger receptor class B type 1 expression had shorter progression-free survival time. Cox analysis indicated that scavenger receptor class B type 1 was an independent prognostic biomarker. In conclusion, our findings implied that scavenger receptor class B type 1 might serve as a diagnostic and independent prognostic biomarker in clear cell renal cell carcinoma.